2021
DOI: 10.1002/advs.202100586
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficiency and Lifetime of Deep‐Blue Hyperfluorescent Organic Light‐Emitting Diode using Pt(II) Complex as Phosphorescent Sensitizer

Abstract: Although the organic light‐emitting diode (OLED) has been successfully commercialized, the development of deep‐blue OLEDs with high efficiency and long lifetime remains a challenge. Here, a novel hyperfluorescent OLED that incorporates the Pt(II) complex (PtON7‐dtb) as a phosphorescent sensitizer and a hydrocarbon‐based and multiple resonance‐based fluorophore as an emitter (TBPDP and ν‐DABNA) in the device emissive layer (EML), is proposed. Such an EML system can promote efficient energy transfer from the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 54 publications
2
54
0
Order By: Relevance
“…[19] In particular, when incorporated with phosphorescent metal complexes or a thermally activated delayed fluorescence (TADF) sensitizer in a hyper-OLED, high efficiency (EQE max = 32.2 %), long lifetime (LT 50 = 156 h at 1000 cd m À 2 ), and narrow FWHM (20 nm) deep-blue OLEDs (CIE y = 0.14) could be realized simultaneously. [20] Thus, given the good spectral overlap between the emission spectrum of 5 and absorption spectrum of the MRF emitter, ν-DABNA (N 7 ,N 7 ,N 13 ,N 13 ,5,9,11,15-octaphenyl-5,9,11,15-tetrahydro-5,9,11,15-tetraaza-19b,20b-diboradinaphtho[3,2,1de:1',2',3'-jk]pentacene-7,13-diamine; Figure S36, Supporting Information), complex 5 may be useful as a sensitizer for the ν-DABNA emitter. We therefore performed photoluminescence decay measurements on mCBP film samples containing 1 wt % ν-DABNA, 10 wt % 5, and ν-DABNA:5 (1 wt %:10 wt % co-doping); the decay curves are presented in Figure S37 (Supporting Information).…”
Section: Organic Light-emitting Diodesmentioning
confidence: 99%
“…[19] In particular, when incorporated with phosphorescent metal complexes or a thermally activated delayed fluorescence (TADF) sensitizer in a hyper-OLED, high efficiency (EQE max = 32.2 %), long lifetime (LT 50 = 156 h at 1000 cd m À 2 ), and narrow FWHM (20 nm) deep-blue OLEDs (CIE y = 0.14) could be realized simultaneously. [20] Thus, given the good spectral overlap between the emission spectrum of 5 and absorption spectrum of the MRF emitter, ν-DABNA (N 7 ,N 7 ,N 13 ,N 13 ,5,9,11,15-octaphenyl-5,9,11,15-tetrahydro-5,9,11,15-tetraaza-19b,20b-diboradinaphtho[3,2,1de:1',2',3'-jk]pentacene-7,13-diamine; Figure S36, Supporting Information), complex 5 may be useful as a sensitizer for the ν-DABNA emitter. We therefore performed photoluminescence decay measurements on mCBP film samples containing 1 wt % ν-DABNA, 10 wt % 5, and ν-DABNA:5 (1 wt %:10 wt % co-doping); the decay curves are presented in Figure S37 (Supporting Information).…”
Section: Organic Light-emitting Diodesmentioning
confidence: 99%
“…34 Recent studies demonstrated that multi-resonance TADF emitters could replace conventional fluorescent dopants to attain high-performance blue-emitting PSF/TASF OLEDs fabricated by vacuum deposition. 35–39 Enlightened by these recent advances, the obstacles of poor solubility of multi-resonance TADF emitters and inefficient ET from the hosts to multi-resonance TADF emitters, which hamper the development of blue SP-OLEDs, could be overcome by incorporating TADF sensitizers in the emitting layers (EMLs) to develop TASF devices.…”
Section: Introductionmentioning
confidence: 99%
“…Such apparent incompatibility between efficient TADF and efficient fluorescence has prompted the development of the socalled hyperfluorescent devices. [8][9][10][11][12] In this approach, both TADF molecules and fluorescent emitters are employed as dopants in a host matrix. The working principle is that after triplet excitons undergo rISC in the TADF molecules, the newly generated singlets may diffuse and transfer to a fluorescent emitter by means of Fo ¨rster resonance energy transfer (FRET).…”
Section: Introductionmentioning
confidence: 99%